2018
DOI: 10.1242/jcs.207985
|View full text |Cite
|
Sign up to set email alerts
|

RDGBα localization and function at membrane contact sites is regulated by FFAT–VAP interactions

Abstract: Phosphatidylinositol transfer proteins (PITPs) are essential regulators of PLC signalling. The PI transfer domain (PITPd) of multi-domain PITPs is reported to be sufficient for function, questioning the relevance of other domains in the protein. In photoreceptors, loss of RDGBα, a multi-domain PITP localized to membrane contact sites (MCSs), results in multiple defects during PLC signalling. Here, we report that the PITPd of RDGBα does not localize to MCSs and fails to support function during strong PLC stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 48 publications
(70 reference statements)
2
32
0
Order By: Relevance
“…Thus our data clearly support a role 395 for dEsyt in supporting the lipid transfer function of RDGB at ER-PM contact sites in vivo. 396 Consistent with this model, we found that the dEsyt protein is localized to the base of the 397 microvillar PM at the ER-PM contact site where the RDGB protein is also specifically 398 localized (Vihtelic et al, 1993;Yadav et al, 2018). 399 400 Although we found a normal density of ER-PM MCS in dEsyt KO photoreceptors at eclosion, 401…”
supporting
confidence: 62%
“…Thus our data clearly support a role 395 for dEsyt in supporting the lipid transfer function of RDGB at ER-PM contact sites in vivo. 396 Consistent with this model, we found that the dEsyt protein is localized to the base of the 397 microvillar PM at the ER-PM contact site where the RDGB protein is also specifically 398 localized (Vihtelic et al, 1993;Yadav et al, 2018). 399 400 Although we found a normal density of ER-PM MCS in dEsyt KO photoreceptors at eclosion, 401…”
supporting
confidence: 62%
“…Through this method, we determined the levels of PIP and PIP 2 in retinal samples. As a positive control, we studied the levels of PI, PIP and PIP 2 in retinae from rdgB mutants; rdgB encodes an eye-enriched phosphatidylinositol transfer protein (Trivedi and Padinjat, 2007) that is required to support PI(4,5)P 2 resynthesis during phototransduction (Hardie et al, 2001(Hardie et al, , 2015Yadav et al, 2015Yadav et al, , 2018. Using our assay, we found that the levels of 36:2 and 36:3 species of PIP and PIP 2 , which were the most abundant species in retinal tissue ( Fig.…”
Section: Depletion Of Pi4kiiiα Reduces Pip and Pip 2 Levels In Photormentioning
confidence: 97%
“…Phospholipid exchange occurs between ER and the PM at RdgBα-enriched ER-PM MCSs ( Cockcroft and Raghu, 2016 ; Cockcroft et al, 2016 ). The clustering of RdgBα at these ER-PM contact sites involves its FFAT motif, which enables RdgBα recruitment by Drosophila VAP-A ( Yadav et al, 2018 ). Moreover, the absence of VAP-A leads to RdgBα mis-localization, preventing it from performing its function at ER-PM MCSs thereby disrupting phototransduction ( Yadav et al, 2018 ).…”
Section: The Cellular Coordination Of Phospholipid Metabolism and Tramentioning
confidence: 99%